2016
DOI: 10.1038/srep28070
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Control of Zika as a Mosquito-Borne and Sexually Transmitted Disease: A Mathematical Modeling Analysis

Abstract: The ongoing Zika virus (ZIKV) epidemic in the Americas poses a major global public health emergency. While ZIKV is transmitted from human to human by bites of Aedes mosquitoes, recent evidence indicates that ZIKV can also be transmitted via sexual contact with cases of sexually transmitted ZIKV reported in Argentina, Canada, Chile, France, Italy, New Zealand, Peru, Portugal, and the USA. Yet, the role of sexual transmission on the spread and control of ZIKV infection is not well-understood. We introduce a math… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
265
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(285 citation statements)
references
References 37 publications
13
265
1
Order By: Relevance
“…It generally results in a mild disease characterized by low-grade fever, rash, and/or conjunctivitis, although only ∼20% of those infected are symptomatic (4). Although there have been instances of sexual and perinatal/vertical transmission (5)(6)(7)(8)(9)(10)(11)(12) and the potential for transmission by transfusion is present (13), ZIKV spreads primarily through infected Aedes mosquitoes (14,15).…”
mentioning
confidence: 99%
“…It generally results in a mild disease characterized by low-grade fever, rash, and/or conjunctivitis, although only ∼20% of those infected are symptomatic (4). Although there have been instances of sexual and perinatal/vertical transmission (5)(6)(7)(8)(9)(10)(11)(12) and the potential for transmission by transfusion is present (13), ZIKV spreads primarily through infected Aedes mosquitoes (14,15).…”
mentioning
confidence: 99%
“…Padmanabhan et al (2017), consider two classes of human infectious, asymptomatic and symptomatic, which are assumed to be equally infectious and of similar du-ration (period of infectiousness) [24]. Onuorah et al (2016) suggest a deterministic mathematical model of ZIKV where obtained the R 0 using the next generation method [25], indicating to be most sensitive to the biting and mortality rate of mosquitoes while sexual transmission increases the risk of infection and epidemic size and prolongs the outbreak [26].…”
Section: Introductionmentioning
confidence: 99%
“…Ebenezer et al [21] suggested that to control disease the best strategy is to combine all preventive, treatment and Insecticides controls simultaneously. Daozhou et al [22] noted that to control spread of ZIKV preventive steps are necessary during sexual activities in ZIKV outbreak area.…”
Section: Introductionmentioning
confidence: 99%